Gamma glutamyl transpeptidase as a prognostic biomarker in hepatocellular cancer patients especially with >5 cm tumors, treated by liver transplantation. Issue 2 (June 2020) - Ince, Volkan; Carr, Brian I.; Bag, Harika Gozukara; Koc, Cemalettin; Usta, Sertac; Ersan, Veysel; Baskiran, Adil; Sahin, Tevfik Tolga; Yilmaz, Sezai
Background: Serum AFP levels are typically elevated in less than 50% of hepatocellular cancer (HCC) patients. Gamma-glutamyl transpeptidase (GGT) levels have been suggested to be a potentially useful HCC biomarker. Aims: To assess in a cohort of prospectively evaluated HCC patients who underwent liver transplant and whose survival was known; the occurrence, prognosis, and clinical characteristics of patients with elevated serum GGT levels. Results: Serum GGT levels were found to be elevated in a higher proportion in patients with either small or large HCC than alpha-fetoprotein (AFP) levels, and were significantly related to prognosis in patients with large size HCCs. There was no clear correlation between GGT and AFP levels, likely reflecting different HCC characteristics or HCC cell lineages associated with these two markers. Furthermore, elevated GGT was found in 24% of low-AFP patients with small tumors and 46% with large tumors. Elevated GGT levels were also significantly associated with microvascular invasion and tumor diameter. Conclusions: Elevated serum GGT levels were associated with HCC size and worse survival, and were unrelated to AFP levels. GGT may be a useful prognostic tumor marker, especially for low-AFP HCC patients.